Structure, evolution and functional inference on the Mildew Locus O (MLO) gene family in three cultivated Cucurbitaceae spp. (December 2015) - Iovieno, Paolo; Andolfo, Giuseppe; Schiavulli, Adalgisa; Catalano, Domenico; Ricciardi, Luigi; Frusciante, Luigi; Ercolano, Maria; Pavan, Stefano
Abstract Background The powdery mildew disease affects thousands of plant species and arguably represents the major fungal threat for many Cucurbitaceae crops, including melon (Cucumis melo L.), watermelon (Citrullus lanatus L.) and zucchini (Cucurbita pepo L.). Several studies revealed that specific members of theMildew Locus O (MLO ) gene family act as powdery mildew susceptibility factors. Indeed, their inactivation, as the result of gene knock-out or knock-down, is associated with a peculiar form of resistance, referred to asmlo resistance. Results We exploited recently available genomic information to provide a comprehensive overview of theMLO gene family in Cucurbitaceae. We report the identification of 16MLO homologs inC. melo, 14 inC. lanatus and 18 inC. pepo genomes. Bioinformatic treatment of data allowed phylogenetic inference and the prediction of several ortholog pairs and groups. Comparison with functionally characterizedMLO genes and, inC. lanatus, gene expression analysis, resulted in the detection of candidate powdery mildew susceptibility factors. We identified a series of conserved amino acid residues and motifs that are likely to play a major role for the function of MLO proteins. Finally, we performed a codon-based evolutionary analysis indicating a general high level of purifying selection in the three CucurbitaceaeMLO gene families, and the occurrence of regions under diversifying selection in candidate susceptibility factors. Conclusions Results of this study may help to address further biological questions concerning the evolution and function ofMLO genes. Moreover, data reported here could be conveniently used by breeding research, aiming to select powdery mildew resistant cultivars in Cucurbitaceae.